Phase 2 study of TAK-442, an oral factor Xa inhibitor, in patients following acute coronary syndrome - Goldstein, Sidney; Bates, Eric R.; Bhatt, Deepak L.; Cao, Charlie; Holmes, David; Kupfer, Stuart; Martinez, Felipe; Spaeder, Jeffrey; Weitz, Jeffrey I.; Ye, Zhan; Zannad, Faiez; the AXIOM Investigators; on behalf of (Thrombosis and Haemostasis, 2014)
TAK-442 is an oral direct factor Xa inhibitor. We sought to determine the dose-dependent effect of TAK-442 on major bleeding when added to standard treatment in stabilised patients with acute coronary syndrome (ACS). In this phase II double-blind study, 2,753 ACS patients were randomised to TAK-442 or placebo in addition to usual care using a three-stage adaptive design. Patients were randomised to placebo in all stages, but doses of TAK-442 escalated from 10 mg BID, 20 mg twice-daily (BID), or 40 mg once-daily (QD) in stage 1; to 40 mg BID, 80 mg QD, or 80 mg BID in stage 2; and to 160 mg QD or 120 mg BID in stage 3. Study drug was started 36 hours after emergent treatment of ACS and within seven days of admission, and continued for 24 weeks. The primary endpoint was incidence of TIMI (thrombolysis in myocardial infarction) major bleeding. TIMI major bleeding incidence was low, but higher with the pooled TAK-442 doses than with placebo (17 [0.9%] vs 4 [0.5%]; p=0.47), although the difference was neither significant nor dose-dependent. However, a dose response was evident when using the modified ISTH scale. The incidence of cardiovascular events was similar among TAK-442 dose groups and placebo. When administered over a wide range of doses after an ACS event, TAK-442 treatment did not result in a dose-dependent increase in TIMI major bleeding, but increased bleeding was observed when a more sensitive bleeding scale was used. There was no evidence for efficacy.
Keywords: Oral factor Xa inhibitors; acute coronary syndrome; thrombosis